The Relationship of Clean Water Facilities and Fecal Discharge to Incidence of Diarrhea in The Tidal Floods Area and Not Tidal Flood in Pekalongan (Universitas Negeri Semarang, 2019)
Diarrhea is a major health problem in Indonesia. The incidence of diarrhea in Pekalongan increased from 622 patients in 2015 to 1,507 in 2016 and a 10% increase existing 2017. The purpose of the study to analyze the relationship of clean water facilities and fecal discharge to incidence of diarrhea in the tidal floods area and not tidal flood in Pekalongan. The study was conducted with a retrospective approach. The population in this study 2,186 homes were tidal flood. The sample amounted to respectively 96 people in the area tidal flood and 96 in the area do not tidal flood, with purposive sampling techniques. Retrieving data obtained by giving questionnaires and in-depth interviews in the respondents. Bivariat.Hasil data analysis research shows the incidence of diarrhea by 74% tidal flood region while not tidal flood the incidence of diarrhea by 45.8%. Tidal flood can cause a seedy neighborhood and become a breeding ground for bacteria. Water supply contaminated by tidal flooding can cause diarrhea. Tidal flood damage excreta disposal facilities, due to the septic tank is covered with water, so a lot of bacteria that can cause diarrhea. There is a relationship clean water facilities and fecal discharge to incidence of diarrhea in the tidal floods area and not tidal flood. Suggestions community is expected to understand the importance of maintaining healthy clean environment to avoid diarrhea. so many bacteria that can cause diarrhea. There is a relationship relationship of clean water facilities and fecal discharge to incidence of diarrhea in the tidal floods area and not tidal flood. Suggestions community is expected to understand the importance of maintaining healthy clean environment to avoid diarrhea. so many bacteria that can cause diarrhea. There is a relationship diarrhea with clean water facilities and fecal discharge to incidence of diarrhea in the tidal floods area and not tidal flood. Suggestions community is expected to understand the importance of maintaining healthy clean environment to avoid diarrhea.